Penentuan Daerah Potensi Geothermal Dengan Menggunakan Metode Seismik Di Madina - Nazaruddin Nasution (Universitas Negeri Medan, 2020)
ABSTRACT: Puncak Sorik Marapi Subdistrict Area is a highland area which is located at 2,145 meters above sea level at coordinates 0,41- 11 South Latitude and 99,32- 13 East Longitude, in the area under study is the peak area which is still being said relatively flat and can be used as a power plant area. Based on this, it is necessary to conduct the research about the structure of the soil layer. Primary seismic data retrieval is performed at four points which at each point is rare of 200 m. The data obtained were analyzed using MonoST software and then converted to Mseed format using Datapro software, files with Mseed format were processed using Geopsy software. From the data obtained the frequency value of 0.949 Hz to 1.421 Hz concludes that the classification of soil types in the research area is included in soft oil types with surface sediment thickness is very thick. This is in accordance with conditions in the field in the form of geothermal location with silt due to geothermal activity. Data of kg values obtained at points 22.7 – 30.4 at 4 points can be said to be low, it is concludes the seismic vulnerability that will be experience by the research site is insignificant or tends will not happen the fault or landslide if it occurs the earthquake. From the PGA values obtained in the range of 8.3 – 9.1, these values fall into the very small risk category based on the earthquake risk level classification.